KEPEMIMPINAN KEPALA MADRASAH DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM - Cik Na'imah (LPPM STAI Muhammadiyah Probolinggo, 2017)
Principal as the leader of the institution with various functions and roles, of course, an important person is responsible for all the activities as well as forward or backward, good or bad, or whether a quality of education is excellent or not from the education institution that is lead. So it is not surprising that he referred to as the first and foremost on the existence and quality of education that is lead. Especially in the face of competition is so tight, both between educational institutions and output, then steps and educational innovations is something that can not be offered anymore and should be realized